Ms. Muffet, the Spider(gram) and the Web of Macro-Financial Linkages - Cervantes, Ricardo (IMF Working Papers; Working Paper ;, 2014)
The global financial crisis has underscored the importance of understanding macro-financial developments and spillovers in an increasingly interconnected and intricate system. At the IMF, staff is focusing on the linkages between the real economy and the financial sector, as well as the inter-relationships between global and individual-country risks. The Country Financial Stability Map provides an empirical framework for explicitly linking these various aspects of the IMF's surveillance of its member countries. It identifies potential sources of macro-financial risks particular to a country and also enables an assessment of these risks in a global context through comparisons with the corresponding Global Financial Stability Map from the Global Financial Stability Report. The authors have developed an Excel-based tool ('Ms. Muffet') to facilitate this analysis, which may be replicated by external users with access to the necessary databases, using the accompanying template.